2017
DOI: 10.1016/j.zool.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Bone up: craniomandibular development and hard-tissue biomineralization in neonate mice

Abstract: The presence of regional variation in the osteogenic abilities of cranial bones underscores the fact that the mechanobiology of the mammalian skull is more complex than previously recognized. However, the relationship between patterns of cranial bone formation and biomineralization remains incompletely understood. In four strains of mice, micro-computed tomography was used to measure tissue mineral density during perinatal development in three skull regions (calvarium, basicranium, mandible) noted for variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…A possible reason for the failure of metformin to rescue cranial width is that the age-related trajectories throughout the craniofacial bone are affected by the functional specific chemical or physical niches, as well as ontogenetic processes influencing each region. 27 However, our understanding of cranial bone formation at different regions during early development still needs to be further improved. 28 Our results showed that metformin also promoted bone formation of OC-Cre; Pck2 f/f mice femurs at P0 and P5, as assessed by the HE staining (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A possible reason for the failure of metformin to rescue cranial width is that the age-related trajectories throughout the craniofacial bone are affected by the functional specific chemical or physical niches, as well as ontogenetic processes influencing each region. 27 However, our understanding of cranial bone formation at different regions during early development still needs to be further improved. 28 Our results showed that metformin also promoted bone formation of OC-Cre; Pck2 f/f mice femurs at P0 and P5, as assessed by the HE staining (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Some examples are electrospun nanofibrous scaffolds and rapid prototyping technologies such as SLA, DLP, SLS, and 3DP ( Yuan et al, 2017 ; Udomluck et al, 2020 ). Bone matrix production shows differences in endochondral and intramembranous grafts suggesting a site-specific bone formation pattern based on the form of cranial bone ossification ( Thompson et al, 2017 ). Osteoconduction and osteoinduction properties of demineralized bone matrix (DBM), especially from cortical bone have made it a proper osteoinductive matrix ( Ansari, 2019 ).…”
Section: Craniofacial Tissue Engineeringmentioning
confidence: 99%
“…When embryonic muscles contract in fetal movements, they can produce a mechanical load on cartilages and bones. It has been argued that the mechanical load induced by muscles might affect chondrification and ossification in embryonic development (Balanta‐Melo et al, 2019; Conith et al, 2019; Moore, 2010; Sella‐Tunis et al, 2018; Spassov et al, 2017; K. D. Thompson et al, 2017; Weijs & Hillen, 1986). With the invention and application of neuromuscular blocking agents, which cause paralysis of vertebrate embryos, researchers became capable of investigating muscle–bone interaction (Drachman & Coulombre, 1962).…”
Section: Introductionmentioning
confidence: 99%
“…When embryonic muscles contract in fetal movements, they can produce a mechanical load on cartilages and bones. It has been argued that the mechanical load induced by muscles might affect chondrification and ossification in embryonic development (Balanta-Melo et al, 2019;Conith et al, 2019;Moore, 2010;Sella-Tunis et al, 2018;Spassov et al, 2017;K. D. Thompson et al, 2017;Weijs & Hillen, 1986).…”
mentioning
confidence: 99%